Aproximación al proceso migratorio venezolano en el siglo XXI (2019)
The objective of this article is to conduct a documentary review of the academic and scientific production that has been generated from the Venezuelan migratory process from the year 2000 to the present, under a documentary analysis of secondary sources. It is evident that the study of Latin American migratory dynamics is complex and the different theories that have tried to explain it usually include variables such as the demographic transition, the globalization of the media, the cultural dependence and the family networks that are related to the difficulties that these countries have experienced, and have affected employment, real income and economic security, which consequently have incentivized people to migrate. The analysis of the Venezuelan emigration, allows to know this process and the construction of an "other territory" as an appropriate place for controversy of the national identities and for the writing of the relations between migrant individuals and their sociocultural environments.